Adenovirus 5 recovery using nanofiber ion‐exchange adsorbents. Issue 7 (28th March 2019) - Turnbull, Jordan; Wright, Bernice; Green, Nicola K.; Tarrant, Richard; Roberts, Iwan; Hardick, Oliver; Bracewell, Daniel G.
Abstract: Viral vectors such as adenovirus have successful applications in vaccines and gene therapy but the manufacture of the high‐quality virus remains a challenge. It is desirable to use the adsorption‐based chromatographic separations that so effectively underpin the therapeutic protein manufacture. However fundamental differences in the size and stability of this class of product mean it is necessary to revisit the design of sorbent's morphology and surface chemistry. In this study, the behaviour of a cellulose nanofiber ion‐exchange sorbent derivatised with quaternary amine ligands at defined densities is characterised to address this. This material was selected as it has a large accessible surface area for viral particles and rapid process times. Initially, the impact of surface chemistry on infective product recovery using low (440 µmol/g), medium (750 µmol/g), and high (1029 µmol/g) ligand densities is studied. At higher densities product stability is reduced, this effect increased with prolonged adsorption durations of 24 min with just 10% loss at low ligand density versus 50% at high. This could be mitigated by using a high flow rate to reduce the cycle time to 1 min. Next, the impact of ligand density on the separation's resolution was evaluated. Key to understanding virus quality is the virus particle: infectious virus particle ratio. It was found this parameter could be manipulated using ligand density and elution strategy. Together this provides a basis for viral vector separations that allows for their typically low titres and labile nature by using high liquid velocity to minimise both load and on‐column times while separating key product and process‐related impurities. Abstract : Viral vectors such as adenovirus have successful applications in vaccines and gene therapy but the manufacture of the high‐quality virus remains a challenge. It is desirable to use the adsorption‐based chromatographic separations that so effectively underpin the therapeutic protein manufacture. A cellulose nanofiber approach to the capture of adenovirus using an ion exchange ligand at three ligand densities was used to understand those parameters impacting recovery and resolution. Critically a time dependency to the recovery of infective virus was found, ligand density had a strong interaction with this behaviour as well as strongly effecting retention time. By understanding these phenomena capture with high recovery of this viral vector was achieved.